2016
DOI: 10.1051/meca/2015075
|View full text |Cite
|
Sign up to set email alerts
|

Cold expansion process on hard alloy holes-experimental and numerical evaluation

Abstract: This paper presents an evaluation of the influence of the cold expansion process on the fatigue performance of holes in hard alloys, as such materials are involved in an increasing number of aeronautical applications. Fatigue enhancement could bring significant savings for numerous possible industrial applications. However, although the cold expansion of aluminium holes has been studied widely, there have been few publications concerning this process in hard alloys and there is currently very few research acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In the present problem, axisymmetric modeling appeared to be sufficiently representative of the phenomena operating over the vast majority of expanded sections, at least those that would be the most loaded during subsequent use. In previous work using these models, we obtained results that were very reliable compared with experimental results . So, in this study, we decided to develop other axisymmetric models of the process.…”
Section: Modeling Strategy For Simulation Of Multiple Cold Expansion mentioning
confidence: 97%
See 1 more Smart Citation
“…In the present problem, axisymmetric modeling appeared to be sufficiently representative of the phenomena operating over the vast majority of expanded sections, at least those that would be the most loaded during subsequent use. In previous work using these models, we obtained results that were very reliable compared with experimental results . So, in this study, we decided to develop other axisymmetric models of the process.…”
Section: Modeling Strategy For Simulation Of Multiple Cold Expansion mentioning
confidence: 97%
“…In the aeronautical industry, Ti‐6Al‐4V alloys are found in the great majority of titanium structural applications and are, therefore, considered in this study. As it can be seen in a previous article, few studies describe the implementation of expansion processes for hard alloys in the literature . No precise analysis of the response of hard metals subjected to expansion is reported and only studies of specific cases can be found, although generic processes designed for the expansion of holes in aluminum alloys are considered.…”
Section: Introductionmentioning
confidence: 99%
“…V. Archard et al [13] assessed the influence of the cold expansion ratios on the fatigue strength of Ti-6Al-4V tensile specimens by conducting an experimental and numerical study. The aim of the study was to understand the impact of the high-expansion ratio in titanium holes and the influence on fatigue performance.…”
Section: Introductionmentioning
confidence: 99%